The Effect of Pumpkin Flour Filler Substitution on the Nutrition Facts of Beef Sausage - Prayitno, Agus Hadi; Miskiyah, Firdha; Soeparno, Soeparno (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The objectives of the experiment were to determine the effect of pumpkin flour filler substitution on the nutrition facts of beef sausage. The research material was divided into five substitution treatments of pumpkin flour as a filler in sausage processing, namely: 0, 25, 50, 75, and 100% of the total filler. Each treatment consisted of five replications. The nutrition facts of sausages was calculated based on the nutritional adequacy rate of sausages which refers to the average energy sufficiency for the Indonesian population per person per day, which is 2,150 kcal, total protein 60 g, total fat 67 g, and 30 g food fiber with a 50 g serving size. The data from the calculation of the nutrition facts of sausages were analyzed by analyzing variance and then tested by using Duncan's New Multiple Range Test. The results showed that the sausages substituted filler with pumpkin flour had a highly significant effect (P<0.01) on total protein, fiber, and β-carotene, but did not affect the energy from fat and total fat of beef sausage. Sausages substituted filler with pumpkin flour up to 100% had a higher intake of total protein, fiber, and β-carotene than control sausages.